Tonal cues modulate line bisection performance: preliminary evidence for a new rehabilitation prospect? - Ishihara, Masami; Revol, Patrice; Jacquin-Courtois, Sophie; Mayet, Romaine; Rode, Gilles; Boisson, Dominique; Farnè, Alessandro; Rossetti, Yves (Frontiers in Psychology, 2013)
The effect of the presentation of two different auditory pitches (high & low) on manual line-bisection performance was studied to investigate the relationship between space and magnitude representations underlying motor acts. Participants were asked to mark the midpoint of a given line with a pen while they were listening a pitch via headphones. In healthy participants, the effect of the presentation order (blocked or alternative way) of auditory stimuli was tested (Exp. 1). The results showed no biasing effect of pitch in blocked-order presentation, whereas the alternative presentation modulated the line-bisection. Lower pitch produced leftward or downward bisection biases whereas higher pitch produced rightward or upward biases, suggesting that visuomotor processing can be spatially modulated by irrelevant auditory cues. In Exp. 2, the effect of such alternative stimulations in line bisection in right brain damaged patients with a unilateral neglect and without a neglect was tested. Similar biasing effects caused by auditory cues were observed although the white noise presentation also affected the patient’s performance. Additionally, the effect of pitch difference was larger for the neglect patient than for the no-neglect patient as well as for healthy participants. The neglect patient’s bisection performance gradually improved during the experiment and was maintained even after one week. It is therefore concluded that auditory cues, characterized by both the pitch difference and the dynamic alternation, influence spatial representations. The larger biasing effect seen in the neglect patient compared to the no-neglect patient and healthy participants suggests that auditory cues could modulate the direction of the attentional bias that is characteristic of neglect patients. Thus the alternative presentation of auditory cues could be used as rehabilitation for neglect patients. The space-pitch associations are discussed in terms of a generalized magnitude system.